Potential and Prospects of Research at the German Archaeological Institute - the German Archaeological Institute, Board of directors of (e-Forschungsberichte des DAI, 2019)
With the establishment of the Instituto di corrispondenza archeologica in Rome in 1829, the foundation stone was laid for the German Archaeological Institute. The 190th anniversary celebration in 2019 was an opportunity for a discussion about shared research perspectives for the Institute‘s departments and commissions. The drafting of the research programmes and their review by the scientific committees of the various departments and commissions was accompanied in the board of directors by a discussion process focused on shared research objectives and future prospects. This discussion additionally served to determine the Institute‘s own position in the context of debates – taking place within various disciplines as well as beyond their boundaries – about the content, methods and tasks of archaeology in the 21st century. This document outlines basic principles as an aid for the development of collaborative research formats at the DAI and to further discuss and refine its research agendas and the vision of the future they contain.